Sustainable application of GF-6 WFV satellite data in desert steppe: A village-scale grazing study in China - Zhang, Yuxun; Wang, Lei; Yang, Xinguo; Sun, Yuan; Song, Naiping (Frontiers in Environmental Science, 2023)
Desert steppe is an essential part of the global grassland ecosystem and plays an essential role by separating other ecosystems as an ecological barrier. Timely and accurate assessment of the growth status of vegetation and change trends in desert grassland areas is needed to avoid waste and overuse of grassland resources. Ningxia Hui Autonomous Region, located in northwest China, has a wide area of desert steppe. The fragility of the environment restricts the coordinated management of ecological resources and production in this region. This paper establishes a model for estimating above-ground biomass (AGB) based on remote sensing images from the Gaofen-6 satellite, combined with canopy spectra and AGB data of vegetated desert steppe areas. Next, the model was used to estimate the time series changes of AGB in the study area in 2020. The ecological carrying capacity and load of the desert steppe area were analyzed based on the number of sheep raised in different enclosures and the grazing methods employed. The status of the forage-livestock balance in the study area was assessed after measuring the crop yield of farmland. Finally, data and case support for grazing management in desert steppe were provided in combination with the research results. The study concluded that Gaofen-6 satellite images could quickly and accurately obtain information on vegetation growth and changes in desert grassland areas at a village scale. The available grazing time in a single year in the study area is inadequate to support current stocking levels. When ecological stability is the primary consideration, natural forage obtained through natural conditions cannot meet the needs of farmers for normal grazing and production activities. The suitable grazing time in the study area is limited in any year. The suitable maximum grazing intensity among all plots ranged from 0.334 to 2.541 sheep/ha. In the case of the balance between grass and livestock, the forage obtained from natural pastures could only satisfy 41.71% of the current stocking levels for sheep. Rotational grazing and subsidies for farmers help desert steppe to recover and achieve a forage-livestock balance.